L'opera italiana nel '700 - Weiss, Piero; Mellace, Raffaele 1969- (Roma Astrolabio, 2013)
This study on the origin and development of eighteenth-century Italian opera in Italy owes its novelty and freshness to its origin in a direct scouring of the documents in the libraries of the Neapolitan conservatories and the major Italian musical institutions associated with eighteenth-century opera in music.(Translated with DeepL.com)
Published posthumously.
Includes bibliographical references (pages 276-285) and index.
Ex libris Nicholas Cornia
Keywords: 18th Century (1701-1800); Opera; Italy